2019
DOI: 10.1140/epjc/s10052-019-7044-5
|View full text |Cite
|
Sign up to set email alerts
|

Compact objects in conformal nonlinear electrodynamics

Abstract: In this paper we consider a special case of vacuum non-linear electrodynamics with a stress-energy tensor conformal to the Maxwell theory. Distinctive features of this model are: the absence of dimensional parameter for non-linearity description and a very simple form of the dominant energy condition, which can be easily verified in an arbitrary pseudo-riemannian space-time with the consequent constrains on the model parameters. In this paper we analyse some properties of astrophysical compact objects coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Birefringence properties were found in [81] with results for conformal theories in accord with those of [3]. The coupling to gravity was considered in [82], and it was shown that a certain condition on black hole charges restricts the form of the conformal electrodynamics Lagrangian density to a one-parameter…”
Section: Jhep03(2021)022mentioning
confidence: 60%
See 2 more Smart Citations
“…Birefringence properties were found in [81] with results for conformal theories in accord with those of [3]. The coupling to gravity was considered in [82], and it was shown that a certain condition on black hole charges restricts the form of the conformal electrodynamics Lagrangian density to a one-parameter…”
Section: Jhep03(2021)022mentioning
confidence: 60%
“…Another solution of the 'universal' PDE yields, in 4D, the new one-parameter generalization of the Born-Infeld theory discussed in [3]; one of its features is that the weak-field The constant factor of e −γ can be removed by a rescaling of the fields, so the restricted conformal electrodynamics Lagrangian density of [82] is, for 2c 2 ≤ 1 and prior to coupling to gravity, equivalent to the duality-invariant ModMax electrodynamics of [3], despite the fact that duality invariance was not assumed in [82].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should remark here that the coupling of generic nonlinear four-dimensional conformal electrodynamics theories to gravity has been investigated in [6], where it was shown that a certain condition on black hole charges restricts the form of any conformal electrodynamics Lagrangian to a particular one-parameter extension of the Maxwell case. As we observed in [5], this class of conformal electrodynamics includes (after a constant rescaling of the gauge potential A m ) the conformal and duality-invariant ModMax theory.…”
Section: Jhep10(2021)031mentioning
confidence: 99%
“…The same symmetry in a NED field theory also yields a traceless energymomentum tensor. This fact has been studied in [6] as well as in [32][33][34][35].…”
Section: Introductionmentioning
confidence: 98%